Catecholaminergic and cholinergic systems of mouse brain are modulated by LMN diet, rich in theobromine, polyphenols and polyunsaturated fatty acids. Issue 4 (10th March 2015) - Fernández-Fernández, Laura; Esteban, Gerard; Giralt, Mercedes; Valente, Tony; Bolea, Irene; Solé, Montse; Sun, Ping; Benítez, Susana; Morelló, José Ramón; Reguant, Jordi; Ramírez, Bartolomé; Hidalgo, Juan; et al.
Abstract : LMN diet could benefit the cognitive reserve reducing Alzheimer's disease risk. Abstract : The possible modulatory effect of the functional LMN diet, rich in theobromine, polyphenols and polyunsaturated fatty acids, on the catecholaminergic and cholinergic neurotransmission, affecting cognition decline during aging has been studied. 129S1/SvlmJ mice were fed for 10, 20, 30 and 40 days with either LMN or control diets. The enzymes involved in catecholaminergic and cholinergic metabolism were determined by both immunohistological and western blot analyses. Noradrenalin, dopamine and other metabolites were quantified by HPLC analysis. Theobromine, present in cocoa, the main LMN diet component, was analysed in parallel using SH-SY5Y and PC12 cell lines. An enhanced modulatory effect on both cholinergic and catecholaminergic transmissions was observed on 20 day fed mice. Similar effect was observed with theobromine, besides its antioxidant capacity inducing SOD-1 and GPx expression. The enhancing effect of the LMN diet and theobromine on the levels of acetylcholine-related enzymes, dopamine and specially noradrenalin confirms the beneficial role of this diet on the "cognitive reserve" and hence a possible reducing effect on cognitive decline underlying aging and Alzheimer's disease.